Self Efficacy, Goal Commitment and Sales Performance Among Insurance Sales Agents in Mombasa, Kenya - Njagi, Zippy Mukami; Lagat, Charles; Korir, Michael (European Scientific Journal, ESJ, 2019)
The purpose of this study was to examine the Mediation effect of goal commitment on the relationship between self-efficacy and sales performance. The study adapted explanatory research design targeting 448 insurance Sales Agents in Mombasa County, Kenya. Using self-administered questionnaires, reliability test of the research instrument was done by the use of Cronbach. Pearson Correlation and conditional process analysis, model 4 was used to analyze the data and to test the hypotheses. The study found that self-efficacy and goal commitment had a positive and significant direct effect on sales performance. Further, the study confirmed a Mediating effect of goal commitment on the indirect relationship between self-efficacy and sales performance. The findings of the study confirm a positive effect of selfefficacy on sales performance and goal commitment. Goal commitment was also found to positively affect Sales Performance. Furthermore, the result confirms the Mediating effect of Goal commitment on the relationship between Self-Efficacy and Sales Performance. Managers and policy makers should therefore put strategies in place that help their sales persons to know the right thing to do in every selling situation. This can be done through indoor training programs as it helps them feel confident of their ability to perform their sales job well and effectively.